2013
DOI: 10.1364/ol.38.005212
|View full text |Cite
|
Sign up to set email alerts
|

2  GHz passively harmonic mode-locked fiber laser by a microfiber-based topological insulator saturable absorber

Abstract: We report on the generation of passive harmonic mode locking of a fiber laser using a microfiber-based topological insulator (TI) Bi(2)Te(3) saturable absorber (SA). The optical deposition method was employed to fabricate the microfiber-based TISA. By virtue of the excellent nonlinear optical property of the proposed TISA, the fiber laser could operate at the pulse repetition rate of 2.04 GHz under a pump power of 126 mW, corresponding to the 418th harmonic of fundamental repetition frequency. The results demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
217
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 432 publications
(223 citation statements)
references
References 30 publications
3
217
1
2
Order By: Relevance
“…As in Ref. 52, Luo et al demonstrated the combination of high nonlinearity induced by the real part of third-order nonlinear optical property in passively mode-locked fiber lasers with high-repetition rates. The SPF-based SAs have the merits of high power tolerance and longer light-matter interaction length, but the SPF requires accurate polishing technique and usually causes unwanted polarization-dependent insertion loss.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…As in Ref. 52, Luo et al demonstrated the combination of high nonlinearity induced by the real part of third-order nonlinear optical property in passively mode-locked fiber lasers with high-repetition rates. The SPF-based SAs have the merits of high power tolerance and longer light-matter interaction length, but the SPF requires accurate polishing technique and usually causes unwanted polarization-dependent insertion loss.…”
Section: Introductionmentioning
confidence: 87%
“…Several methods have been used to obtain the TMD SAs, such as solution processing method, 84 evanescent field-interaction method, 39,52 composite films composed of nanomaterial flakes in a polyvinyl alcohol (PVA) host, 43,53 and the bottom-up growth techniques such as chemical vapor deposition (CVD), 92,99 pulsed laser deposition (PLD), [63][64] and the magnetron sputtering technique (MST). [60][61] In the laser cavity, these SAs are usually pasted on fiber ferrules, or embedded in the air channels of photonic crystal fiber (PCF), 30,36,67,77,108,[119][120][121][122][123][124] or deposited on microfiber or side polished fiber (SPF).…”
Section: Introductionmentioning
confidence: 99%
“…126 In many cases, bismuth chalcogenides are used in the form of powders 127 or microfibers, 125,128-132 which do not exhibit TSS. Therefore, the efficiency of antimony or bismuth chalcogenides as saturable absorbers 125,128,131,[133][134][135][136][137][138][139][140] has nothing related to topological phases of matter, in spite of the wealth of claims in the literature. Nevertheless, in the following we briefly discuss the most important findings of this research topic.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…To obtain ultrashort pulses, the laser generally require a saturable absorber to achieve the mode locking mechanism. Various approaches have been developed since the early days of ultrafast lasers including physical light intensity absorbers such as semiconductor saturable absorption mirrors (SESAMs) [6], [7], carbon nanotubes [8], [9], graphene [10], [11], topological insulators [12], [13], black phosphorous [14], [15], and most recently transition-metal dichalcogenides (TMDs) [16], [17]. However, these physical absorbers either have bandwidth limitation or stability issues.…”
Section: Introductionmentioning
confidence: 99%